Determinants of Customer Satisfaction and Service Quality-The Case of Romanian Public Services- - Horia Mihai RABOCA (Transylvanian Review of Administrative Sciences, 2006)
The present study portrays customer satisfaction and service quality as a multidimensional construct and investigates the link between customer satisfaction determinants and service quality determinants. Based on arguments that customer satisfaction should be operationalized along the same determinants/factors and dimensions (and the corresponding items) on which service quality is operationalized, the results of study indicate that the two constructs are indeed independent but closely related, implying that an increase in one is likely to lead to an increase in another.